Unveiling nitrogen preferences in indica rice: a classification study of cultivars in South China - Lu, Chu-sheng; Lai, Jia-jun; Fan, Xian-ting; Liang, Kai-ming; Yin, Yuan-hong; Ye, Qun-huan; Shen, Hong; Fu, You-qiang (Frontiers in Plant Science, 2025)
IntroductionDo indica rice cultivars prefer ammonium or nitrate? Understanding this preference is key to optimizing nitrogen use efficiency in rice production. Ammonium and nitrate are crucial for plant nitrogen nutrition, as rice cultivars exhibit varying preferences. However, few studies have classified ammonium and nitrate preferences within indica cultivars.MethodsFor the first time, this study classifies indica rice cultivars based on their ammonium and nitrate preferences, revealing significant differences in biomass production under various nitrogen treatments. This study investigated the effects of ammonium-only nutrition (100:0), ammonium-nitrate mixed nutrition (75:25), and nitrate-only nutrition (0:100) on the maximum root length, shoot length, SPAD value, and biomass of 24 widely cultivated indica cultivars in South China.ResultCompared to ammonium-only nutrition, a mixed ammonium-nitrate treatment significantly boosted root and shoot growth, while nitrate-only nutrition led to a decline in chlorophyll content. Compared with the 100:0 treatment, the maximum root length, shoot length, root dry weight, shoot dry weight, and total dry weight in the 75:25 treatment significantly increased by 29.85%, 4.11%, 7.65%, 1.71% and 3.03% (p < 0.01), respectively; and the SPAD value in the 0:100 treatment significantly decreased by 4.22% (p < 0.01).DiscussionThese results demonstrate distinct responses of rice cultivars to different nitrogen treatments. Through correlation, principal component, and cluster analyses, the rice cultivars were categorized into three types: ammonium-preferring type (APT), ammonium- and nitrate-preferring type (ANPT), and nitrate-preferring type (NPT). The APT, ANPT, and NPT showed the highest biomass in the 100:0, 75:25, and 0:100 treatments, respectively, with the biomass in the ANPT significantly exceeding that of the APT (p < 0.01). These insights provide a foundation for breeding high-yield indica rice, optimizing nitrogen fertilizer strategies, and improving nitrogen use efficiency in sustainable agriculture.